Intelligence, creativity and fantasy : proceedings of the 5th International Multidisciplinary Congress (PHI 2019), October 7-9, 2019, Paris, France /: proceedings of the 5th International Multidisciplinary Congress (PHI 2019), October 7-9, 2019, Paris, France. (2019) - Unknown
No abstract available